HUBUNGAN KEKUATAN OTOT LENGAN DAN OTOT TUNGKAI DENGAN KETEPATAN PUKULAN JUMPING SMASH BULUTANGKIS - Apif Hakam Ponsamwijaya; Rubiyatno; Putra Sastaman B. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of arm and leg muscle strength on the accuracy of the jumping smash in badminton. This research method utilizes a quantitative approach with correlation techniques to identify the relationship between muscle strength variables and shot accuracy. The sample in this study consisted of 12 students of MAN Insan Cendekia Sambas who participated in badminton extracurricular activities. The analysis showed that arm muscle strength did not significantly influence the accuracy of the jumping smash, with a correlation value of 0.004. In contrast, leg muscle strength was shown to significantly influence the accuracy of the jumping smash, with a correlation value reaching 0.858. The results of this study indicate that explosive leg muscle strength has a greater influence on the accuracy of the jumping smash compared to arm muscle strength. Therefore, a training program that focuses on increasing leg muscle strength is highly recommended to improve badminton athletes' ability to execute the jumping smash.